How To Be a World Explorer - Joel Levy & James Gulliver Hancock & Lonely Planet
How to be a World Explorer shows young readers how to venture thru' all the landscapes on earth - the air, over the seas, under the waves - plus how to find food and water in the wild, avoid deadly diseases, fight back against man-eating beasts! Packed with colourful quirky illust.; Essential tips and fun facts on survival in the great outdoors.